Feminism and film in transition in Spain: Margarita y el lobo (1969) and Vámonos, Bárbara (1978), by the director Cecilia Bartolomé - Val Cubero, Alejandra (GénEroos, 2021)
Cecilia Bartolomé´s Margarita y el lobo (1969) and Vámonos, Bárbara (1978) are key pieces of work that help us understand the resistance practices that were ongoing in the sixties and seventies against the Franco regime. Both pieces point out the complexity of gender relations and detail class relations and the power that some institutions, such as the Church, had on Spanish society as a whole and, particularly, on the lives of women. Margarita y el lobo and Vámonos, Bárbara were the starting points of a new brave filmography that influenced important aspects of the emancipation of women and they remain key references in order to understand the difficulties that female movements found during the Spanish dictatorship and during the early years of the Transition period. The aim of the article is to show how Cecilia Bartolomé fought for the emancipation of women and the democratization of the Spanish society in the last years of the Spanish Dictatorship and the first years of the Democracy through her films. In these years, the end of the sixties and beginning of the seventies, women’s associations were timidly being formed, most of them in secret, and they were advocating for legislative and labor reforms in favor of women’s rights. We can venture the hypothesis that Cecilia Bartolome was not oblivious to the profound changes taking place in Spanish society at the time and, therefore, her works were influenced by the feminist assumptions that were in vogue at the time.